2004
DOI: 10.1002/hep.20131
|View full text |Cite
|
Sign up to set email alerts
|

Variation of hepatic glucuronidation: Novel functional polymorphisms of the UDP-glucuronosyltransferase UGT1A4

Abstract: UDP-glucuronosyltransferases are a family of drug metabolizing enzymes contributing to hepatic drug metabolism and protection against environmental toxins. The aim of this study was to identify polymorphisms at the human UGT1A gene locus and to characterize their function and potential association with hepatocellular carcinoma (HCC). Genomic DNA from the blood of 363 subjects (128 patients with HCC, 235 blood donors) was analyzed for polymorphisms of the UGT1A3, UGT1A4, UGT1A8, UGT1A9, UGT1A10 genes using poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
138
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(157 citation statements)
references
References 35 publications
(76 reference statements)
9
138
6
Order By: Relevance
“…Several mutants were expressed in COS-7 cells, and it was determined that contrary to several UGT mutants with diminished activity, the UGT1A3 variants W11R and W11R þ V47A exhibited much greater activity toward estrone than the wild type. The same SNPs were concurrently reported by another group, where the authors additionally characterized the prevalence of these polymorphisms in 470 healthy controls and 258 hepatocellular carcinoma (HCC) patients (Ehmer et al, 2004). No significant difference was found in the allele frequencies between controls and cancer patients.…”
Section: Ugt1a3mentioning
confidence: 61%
See 2 more Smart Citations
“…Several mutants were expressed in COS-7 cells, and it was determined that contrary to several UGT mutants with diminished activity, the UGT1A3 variants W11R and W11R þ V47A exhibited much greater activity toward estrone than the wild type. The same SNPs were concurrently reported by another group, where the authors additionally characterized the prevalence of these polymorphisms in 470 healthy controls and 258 hepatocellular carcinoma (HCC) patients (Ehmer et al, 2004). No significant difference was found in the allele frequencies between controls and cancer patients.…”
Section: Ugt1a3mentioning
confidence: 61%
“…Table 2 summarizes some functionally relevant UGT1A3 polymorphisms. The allele frequencies reported in two independent studies are similar, despite the different populations characterized in each study (Ehmer et al, 2004;Iwai et al, 2004). Iwai et al (2004) reported six single-nucleotide polymorphisms (SNPs) in exon 1 of UGT1A3.…”
Section: Ugt1a3mentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, this polymorphism causes an increase of glucuronidation activity. It has been reported that the frequency of UGT1A4 (142T>G) polymorphism is 8% in Caucasians 20) and 12% in Japanese, 21) no marked difference. On the other hand, the frequency of UGT2B7*2 (802C>T) polymorphism, which is linked with −161C>T, 22) was reported to be 48.9-53.7% 23,24) in Caucasians and only 24.4-29.3% 24,25) in Japanese.…”
Section: Discussionmentioning
confidence: 98%
“…Significant individual variations in the conjugation profile, involving glucuronyltransferase isoforms such as UGT1A4 and UGT2B7 are respectively involved in the metabolism of anastrozole and letrozole (41)(42)(43). Glucuronidation profile by UGT1A4 was correlated to therapeutic efficacy of anastrozole in women with breast cancer (44).…”
Section: Drug Interactionsmentioning
confidence: 99%